SITUATIONAL ANALYSIS OF CHILD SEXUAL ABUSE AND EXPLOITATION: THE CASE OF JIMMA AND AGARO TOWNS OF OROMIA REGIONAL STATE - Abashula, Gudina; Jibat, Nega (European Scientific Journal, ESJ, 2014)
This study was conducted to assess people’s awareness, patterns, community responses and factors for child sexual abuse and exploitation in Jimma and Agaro town. Survey, key informant interview and case studies were used to collect the information required for the study. The data collected was analyzed using percentages and case studies under themes developed based on the research objectives. The findings of the study revealed that eighty nine percent of the respondents are aware of the existence of child sexual abuse in their community and more than half of them have identified sexual intercourse with children, child pornography and child genital stimulation as child sexual abuses. Both girls and boys can be exposed to child sexual abuse; however, girls are more vulnerable to child sexual abuses than boys. In terms of their backgrounds, street children, orphans and children of the poor families are mainly vulnerable to child sexual abuse. Children are sexually abused in their home, in the community and in organizations as the findings from the case studies and key informant interviews indicated. Death of parents, family poverty and the subsequent inability to fulfill the necessary basic needs for children; abusers’ perception about sexual affairs with children is safe as they think children are free from HIV/AIDS, lack of appropriate care and follow up for children are the major factors for child sexual abuse. Moreover, the fact that the poor families and their girl children are easily cheated by gifts in cash and in kind from abusers also make children of such families more vulnerable to sexual abuses than others. The police and the court have been making efforts to punish the offenders. However, the measures ever taken are not adequate when compared with the injury afflict on the children by the offenders. Therefore, strengthening the family economic capacity through income generating activities, families’ close follow up of the daily safety of their children, reunification of the street children to their families/relatives and introduction of mechanisms to investigate cases of child abuses by the court in order to take balanced corrective measures on offenders are recommended based the findings.